B-vitamins reduce the long-term risk of depression after stroke: The VITATOPS-DEP trial - Almeida, O.; Marsh, K.; Alfonso, Helman; Flicker, L.; Davis, T.; Hankey, G. (John Wiley and Son, 2010)
Objective The consumption of certain B-vitamins through diet or supplementation decreases the total plasma concentration of homocysteine (tHcy) and may enhance response to standard antidepressant treatment. It is unclear if treatment with B-vitamins can reduce the long-term prevalence of depression in people at risk, such as stroke survivors. The purpose of this research was to determine if treatment with B-vitamins reduces the hazard of poststroke depression compared with placebo. Methods Randomized, double-blind, placebo-controlled trial of tHcy-lowering treatment with daily folic acid (2 mg), vitamin B6 (25 mg), and vitamin B12 (0.5 mg) for 1 to 10.5 years in survivors of stroke. The primary endpoint was the onset of Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) major depression after randomization. Secondary outcomes were the prevalence of DSM-IV major or minor depression at the end of treatment. Other measured factors included age, gender, poststroke handicap associated with stroke, recurrence of strokes, cognitive impairment, and use of antidepressants. Results Among 273 people who completed the final assessment after 7.1 ± 2.1 years (mean ± standard deviation) of follow up, random assignment to B-vitamins was associated with a lower hazard of major depression compared with placebo (18.4% vs 23.3%, adjusted hazard ratio [HR] = 0.48; 95% confidence interval [CI] = 0.31-0.76) and a trend toward a lower odds of major or minor depression at the end of the trial compared with placebo (19.1% vs 27.7%; adjusted odds ratio [OR] = 0.58; 95%CI = 0.31-1.09). Interpretation Long-term treatment of poststroke survivors with folic acid, B6, and B12 was associated with a reduction in the hazard of major depression in our patient population. If these findings can be validated externally, B-vitamin supplementation offers hope as an effective, safe, and affordable intervention to reduce the burden of poststroke depression. © 2010 American Neurological Association.